Segmentation of Traditional Market Shoppers Based on Store Image in Bandung, Indonesia - Fajar S.A Prabowo; Titis Bariki; Deden Syarif Hidayatullah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2020)
Traditional Market is not only a place to sell and buy, it also a platform that support SMEs and has an important role in the regional economy. In addition to having an economic value, traditional markets in Bandung is also one of the hereditary cultures that have to be preserved. Unfortunately the condition of most traditional markets in Bandung is considered not feasible. The store image that traditional market is a dirty place, slum, smell and other bad things have been attached to most of the traditional markets in Bandung. To minimize this, the government decide to is execute traditional market revitalization to change the traditional market get a better image in shoppers mind. In other words, this revitaliasai want to make the traditional market image to be as god as possible. To get the target, segmentation needs to be done in order to know the profile of each group of traditional market shoppers. So govermance can make more efffective and appropriate policy to the target market. Data were collected by distributing questionnaires to 400 traditional market shoppers. The results of the primary data from the questionnaire were processed using two-step cluster analysis with SPSS 20.0 Based on the ressult, researcher found two major segments among the total respondents. The first segment is apathetic shoppers, those who rarely visit the market and have a more negative perception toward traditional markets. And the second segment is enthusiast shopper, those who more often visit traditional markets and provide more positive percepstion toward traditional markets.